BEBAN KERJA PRAMUSAJI FOOD AND BAVERAGE SERVICE DI HOTEL ASTON AND CONFERENCE CENTER TANJUNG PINANG - Rizky Fauzan; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was conducted with the aim to know the workload waiters and to know of employe waiters ideal, based on the workload than handled in Hotel Aston and Conference Center Tanjung Pinang. Methods used in this study is a method quantitative. The content of this research is obtained by observations and interview against 3 of the responden into a sample. Using a method exponential smoothing, with two exponen in the planning of human resources consisting of exponent workload in produces a product as the work load and exponen time/cyle time to find number of employee who ideal. The result concluded that : 1) based on the observation and interview thas was been done, the authors concluded that the result of calculation work load waiters is 3.648 hours 2) From the whole calculation and the result of observations in the Hotel Aston and Conference Center Tanjung Pinang especially the Food and Beverage Service Department to the number of employees based on work load to be addressed it needs sixth people.Key Word : Workload, Waiters, Number of employees ideal